Silver doping effects on irreversibility field and pinning energy of a FeSe iron based superconductor. (May 2020) - Galluzzi, A; Buchkov, K; Nazarova, E; Leo, A; Grimaldi, G; Pace, S; Polichetti, M
Abstract: We have performed DC magnetic moment measurements as a function of magnetic field m(H) and time m(t) on a FeSeo.94 and a silver doped FeSeo.94 + 6 wt% Ag. In particular, from the m(H) measurements, the field dependence of the critical current density Jc (H) of the samples has been extracted at different temperatures in the framework of the Bean critical state model. Starting from the Jc (H) of the samples, we have studied the influence of the silver doping on the temperature dependence of the irreversibility field Hirr (T) above which the pinning energy is so reduced that the vortices are free to move. The obtained Hirr (T) values have been fitted with the equation Hirr (T) = Hirr (0) (1-T/T*) n whose results have been compared with the literature. After that, we have analyzed the silver doping effects on the field dependence of the pinning energy U(H), extracted from relaxation measurements at different temperatures and magnetic fields, obtaining that both samples undergo to a pinning regime crossover.